Methanol-to-olefin conversion over ZSM-5: influence of zeolite chemical composition and experimental conditions on propylene formation. Issue 5 (4th May 2022) - Sousa, Zilacleide S. B.; Luna, Aderval S.; Zotin, Fátima M. Z.; Henriques, Cristiane A.
Abstract: The transformation of methanol into light olefins over ZSM-5 zeolites with different SiO2 /Al2 O3 molar ratios (SAR) and phosphorus contents was investigated. An increase in the SAR and amount of incorporated phosphorus reduced the acid-site strength and density, which favored catalytic stability and the production of light olefins, mainly propylene. Under an isoconversion of 91%, high propylene/ethylene molar ratios were observed using the zeolite with the highest SAR (i.e., HZ(280)) and the one containing 4 wt.% P (i.e., 4PHZ(30)). However, the latter was less stable when used in a long-term reaction. An experimental design was employed to investigate how the reaction temperature and methanol partial pressure affect the propylene (C3 = ) yield in the reaction catalyzed by the HZ(280) zeolite, which led to a temperature of 475 °C and a methanol partial pressure of 0.04 atm using the proposed model within the experimental design space.